Optimising the mechanism of electroshock treatment on the tensile behaviour of the laser melting deposited Ti55531 alloy - Chang Liu; Haoxing Wang; Jian Zhou; Yan Wen; Lechun Xie; Liqiang Wang; Lin Hua (Virtual and Physical Prototyping)
As an important additive manufacturing method, laser melting deposition (LMD) can be utilised to manufacture many high-property components. In this work, the Ti55531 alloy (Ti-5Al-5V-5Mo-3Cr-1Zr) is manufactured by LMD, and a novel electroshock treatment (EST) is introduced to modify the tensile properties of LMD Ti55531. The microstructure of LMD Ti55531 is an alternating arrangement of columnar and equiaxed β grains. The α phase has not undergone an obvious phase transition after 0.06 s EST, and many fine α phase precipitates with EST time increased to 0.08 s. The reduction of dislocations in the trigeminal grain boundary areas improves the ability to accommodate dislocations and plastic deformation, which improves the elongation of LMD Ti55531 from 14.5% to 17.6% without the loss of tensile strength after 0.06 s EST. The precipitation of the fine α phase in the β phase weakens the ability of the sample to withstand plastic deformation after 0.08 s EST, which reduces the elongation. All results indicate that EST is an effective and novel way to optimising the tensile properties of LMD titanium alloys.